Delegation Decisions in Finance - Holzmeister, Felix; Holmén, Martin; Kirchler, Michael; Stefan, Matthias; Wengström, Erik (Management Science, 2023)
Based on an online experiment with a sample of finance professionals and participants from the general population (acting as clients), we examine drivers and motives of clients’ choices to delegate investment decisions to agents. We find that clients favor delegation to investment algorithms, followed by delegation to finance professionals compensated with an aligned incentive scheme, and lastly to finance professionals receiving a fixed payment for investing on behalf of others. We show that trust in investment algorithms or finance professionals, and clients’ propensity to shift blame on others increase the likelihood of delegation, whereas clients’ own decision-making quality is associated with a decrease in delegation frequency. This paper was accepted by Bruno Biais, finance. Funding: This work was supported by Austrian Science Fund [Grants SFB F63 and Y617-G11], Vetenskapsrådet (Swedish Research Council) [Grant 2015-01713], and Oesterreichische Nationalbank (Austrian National Bank) [Grant 17788]. M. Holmén and E. Wengström acknowledge funding from the Swedish House of Finance. Supplemental Material: Data and the online appendices are available at https://doi.org/10.1287/mnsc.2022.4555 .